Anti-inflammatory effect and the effect on acute pharyngitis rats model of compound Lobelia oral liquid - Liu, Baosong (Saudi J Biol Sci, 2019)
OBJECTIVE: Observe anti-inflammatory effect and the effect on acute pharyngitis rats model induced by ammonia water of compound Lobelia oral liquid, providing experimental basis for its clinical use. METHODS: Use egg white establish foot swelling rats model and use carboxymethyl cellulose establish white blood cell migration rats model. Then observe the anti-inflammatory effect of compound Lobelia oral liquid. Use 15% ammonia spray at pharyngeal establish acute pharyngitis rats model, Visual observation and conduct grading of pharyngeal tissue stimulation in rats, measure the levels of TNF-α and IL-6 in serum. Pharyngeal tissue was taken to observe the morphological changes. RESULT: All dose groups of compound Lobelia oral liquid can reduce the rate of foot swelling of rats at all time points (P < 0.01 or P < 0.05), and significantly reduce the number of white blood cells of rats (P < 0.01); And improve the local hyperemia degree, reduce secretion, reduce local swelling of pharyngeal tissue, reduce the serum TNF-α and IL-6 levels of acute pharyngitis rats with different degrees (P < 0.01 or P < 0.05). CONCLUSION: Compound Lobelia oral liquid has a good anti-inflammatory effect on foot swelling and white blood cell migration rats model, as well as significant improvement effect on acute pharyngitis rats model.